Impact of Environmental, Social and Corporate Governance (ESG) practices in Bulgarian SMEs access to finance - Mladen Manolov; Claudia Nelly Berrones-Flemmig (IU Internationale Hochschule, 2025)
Given the European Union's commitments of achieving net zero by 2050 and advocating Environmental, Social, and Corporate Governance (ESG) targets, ESG is having an increasingly larger impact on businesses (Alamillos & De Mariz, 2022). Various studies have concluded that if a company has a high ESG score, it typically borrows at a cheaper rate, receives more favorable credit terms and conditions, has higher valuation, achieves better financial performance, as well as other benefits relating to its access to finance (Jang et al., 2020; Srivastava et al., 2022; Albuquerque et al., 2019; Friede et al. 2015). The same studies focus, however, predominantly on large companies in developed economies. On the other hand, the issue of the financing gap in Small and Medium-Sized Enterprises (SMEs) is experienced globally and especially in developing economies (World Bank, 2019; PwC, 2021). Given the positive impact of ESG on companies access to finance as found in existing literature and the presence of the SME finance gap in developing economies, this research investigates the impact of ESG practices on Small and Medium-Sized Enterprises access to finance in the context of Bulgaria. An overview of current and planned ESG-related European Union regulations impacting SMEs is provided. With a focus on Bulgarian SMEs, a total of 27 experts in the fields of banking, venture capital, angel investing, SME ownership or management, and ESG consulting were interviewed. This study adds to the limited body of research pertaining to the impact of ESG on SMEs financing in a developing economy setting. The research concluded that Bulgarian SMEs engaged in ESG have better debt and equity financing terms, more opportunities and dedicated channels for receiving financing, as well as benefits adding to their competitiveness, such as better access to international supply chains, reduced firm risk, tax exemptions, ability to attract and retain top talent, and higher potential for top line growth, among others.
Keywords: M; Q; 650; ESG; SME access to finance; sustainable finance; SME financing gap; ESG in developing economies